'Artists Hidden from Human Gaze': Visual Culture and Mysticism in the Nineteenth-Century Convent. Issue 2 (October 2020) - Jordan, Kate
Abstract : This article offers a reading of nineteenth-century Roman Catholic theology through the sacred art produced by and for women religious. The practices and devotions that the article explores, however, are not those that drew from the institutional Church but rather from the legacies of mysticism, many of which were shaped in women's religious communities. Scholars have proposed that mysticism was stripped of its intellectual legitimacy and relegated to the margins of theology by post-Enlightenment rationalism, thereby consigning female religious experience to the politically impotent private sphere. The article suggests, however, that, although the literature of women's mysticism entered a period of decline from the end of the Counter-Reformation, an authoritative female tradition, expressed in visual and material culture, continued into the nineteenth century and beyond. The art that emerged from convents reflected the increasing visibility of women in the Roman Catholic Church and the burgeoning of folkloric devotional practices and iconography. This article considers two paintings as evidence that, by the nineteenth century, the aporias 1 of Christian theology were consciously articulated by women religious though the art that they made: works which, in turn, shaped the creed and culture of the institutional Church. In so doing, the article contributes to the growing body of scholarship on the material culture of religion.